PENDIDIKAN NILAI AGAMA MORAL PADA ANAK USIA DINI DI SEKOLAH SEBAGAI LANGKAH PREVENTIF DEKADENSI MORAL - Ahmad Sahnan; Wahyu Purwasih (QURROTI, 2024)
The rapid flow of globalization and information today causes problems in moral consistency. Preventive steps to resolve this problem can be taken through the internalization of religious and moral values ​​education from early childhood. This article tries to provide alternative steps that can be taken by schools to overcome moral decadence. This research is qualitative research with a library research type of research. The author digs up data and information from various relevant sources then reads, examines and concludes in the form of a description. The researchers' findings show that overcoming moral decadence in schools can be done through 1) the active role of teachers and schools in implementing religious and moral values ​​education. 2) Efforts to instill religious and moral values ​​can be carried out using various methods such as playing, storytelling, singing, storytelling, employment, habituation and example. 3) Parental cooperation is also needed to ensure that the religious and moral values ​​education program runs as well as in school. 4) environmental factors are also an important part because they can influence the development of children's religious and moral values ​​in society.